Systemic vascular resistance and endogenous inhibitors of nitric oxide synthesis in early- compared to late-onset preeclampsia: preliminary findings. (3rd July 2017) - Lucovnik, Miha; Lackner, Helmut Karl; Papousek, Ilona; Schmid-Zalaudek, Karin; Schulter, Guenter; Roessler, Andreas; Moertl, Manfred Georg
ABSTRACT: Objective: To examine systemic vascular resistance index (SVRI), asymmetric (ADMA) and symmetric dimethylarginine (SDMA) levels in preeclampsia at different gestations. Methods: Twenty-four preeclamptic patients (14 at ≥ 34 weeks') and 72 matched healthy controls were included. SVRI was calculated from impedance cardiography measurements. ADMA and SDMA levels were determined using enzyme-linked immunosorbent assay . Results: SVRI and SDMA were higher in preeclampsia overall, in early onset and late onset compared to controls. SVRI was correlated with ADMA and SDMA, respectively. Conclusions: Early-onset and late-onset preeclampsia are both characterized by increased systemic vascular resistance and elevated levels of nitric oxide synthesis inhibitors.